Unilateral CO₂ Reduction Policy with More Than One Carbon Energy Source - Julien Xavier Daubanes; Fanny Henriet; Katheline Schubert (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We examine an open economy's strategy to reduce its carbon emissions by replacing its consumption of coal—very carbon intensive—with gas—less so. Unlike the standard theoretical approach to carbon leakage, we show that unilateral CO2 reduction policies generate a higher leakage rate in the presence of more than one carbon energy source, and may turn counterproductive, ultimately increasing world emissions. We establish testable conditions as to whether a unilateral tax on domestic CO2 emissions increases the domestic exploitation of gas, and whether such a strategy increases global emissions. We also characterize this strategy's implications for climate policy in the rest of the world. Finally, we present an illustrative application of our results to the US.
Keywords: Q58; H73; F18; 330; unilateral climate policy; carbon emission reduction; shale gas; gas-coal substitution; coal exports; carbon leakage; US policy; counter-productive policy